The multifaceted Montessori movement, and its pioneers - Christine Quarfood (Problemy Wczesnej Edukacji)
On the eve of World War I, a new movement took shape, promoting the educational ideas of Maria Montessori. The success story of the Montessori method is well known, but how are we to understand the organizational network surrounding it? This article explores some aspects of the Montessori movement’s early history, drawing on social movement theories. In the first part, I argue that the Montessori movement of the interwar era should be conceptualized as a social movement organization (SMO) with AMI as its social movement infrastructure (SMI) and with its own specific cognitive praxis. In the second part, I approach the movement from another angle, more from the inside so to say, to assess how three Montessori pioneers – Anna Maria Maccheroni, Claude Albert Claremont and Nazareno Padellaro – understood and tried to implement this cognitive praxis. I particularly focus on their widely differing interpretations of Montessorism – the movement’s central creed about the child’s liberation.